Environmental Knowledge, Conservation Attitudes, and Public Perceptions of Human Impacts on Bird Populations: A Survey Study - Victor Zhang (Theoretical and Natural Science, 2026)
Bird population decline is a serious issue under anthropogenic influences of the natural world, making public understanding and knowledge of these issues integral for conservation in the future. The study examined public knowledge of avian ecology alongside anthropogenic threats in key categories among knowledge, attitude, engagement and environmental exposure. The study used a survey consulting 45 participants globally in an assessment of the aforementioned categories. Participants demonstrated strong grasps of basic ecological concepts, but showed variance in questions regarding climate change, light pollution, and noise pollution. Environmental knowledge differed demographically in country, living environment, age, and education, with formal education providing the highest increase in environmental knowledge scores. The findings of this study go to suggest that environmental education approaches should combine factual knowledge with approaches fostering direct exposure to the environment.